Kerusakan Hutan dan Lingkugan Hidup dari Pembangunan dan Pertumbuhan Penduduk (Studi Kasus di Kabupaten Polewali Mandar) - Sukadji Sarbi (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2017)
Polewali Mandar has a wealth of tropical forests,to the extent of reaching 72.814 ha. As a forest ecosystem, it plays a very important role for human development and health.Therefore, a healthy forest is needed that can support human life.Human growth and development, has provided various negative impacts on forest ecosystems.Forest management that has been applied has not been able to maintain the optimal function of forests, the more damaged forests.Many economic interests dominate the implementation of forest management.In order to maintain and restore forest functions optimally from various threats that increasingly necessary reorientation to change the practices of forest resource management and the environment wisely, so that the crisis destruction of forests and the environment can be controlled.To the community and various parties related to the management of forest resources and the environment needed awareness to embody the moral and ethics of the environment.